PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN DIVISI PRODUKSI II PT. KOTA JATI FURINDO JEPARA) - Dewi Erma Rahmawati; Sudharto Prawata Hadi (Jurnal Ilmu Administrasi Bisnis, 2018)
PT. Kota Jati Furindo is a furniture company producing indoor dan outdoor furniture with high quality products. The problem in this research is the amount of achievement of production realization is fluctuative which tend to decrease. That indicates low of employee performance. PT. Kota Jati Furindo needs to pay attention to what matters that can affect employee performance to create a strategy to be able to compete with other furniture companies. The purpose of this study is to identify the influence of compensation and motivation for employee performance. The type of this research is explanatory research. The sample used are 119 respondents who have worked at least 6 months at Production division II PT. Kota Jati Furindo. The sampling techniques is simple random sampling. The data collection technique are questionnaire and literature review. Data analysis techniques are correlation, simple linier regression, multiple linier regression, t and F test with SPSS (Statistical Product and Service Solutions) program version 16.0 The result of this study showed that the compensation has an effect on employee permormance with a correlation coefficient about 0,744 and determination coefficient about 55,4%, motivation itself has an effect on employee performance with a correlation coefficient about 0,646 and determination coefficient about 41,8%. Both compensation and motivation have an effect on employee performance by the equation of Y = -1,243 + 0,464X1 + 0,280X2. This means that the affect of compensation and motivation will improve employee performance. The conclusion of this study is, that compensation and motivation influence the employeeis performance. The recommendation proposed follow. It is necessary to evaluate its compensation system and strengthen the motivation of employee.